2005
DOI: 10.1108/02683940510579759
|View full text |Cite
|
Sign up to set email alerts
|

Assessing leadership styles and organisational context

Abstract: Purpose -To investigate the new leadership dimensions questionnaire (LDQ) and a related framework for assessing an individual's leadership style in relation to the context in which the leader works; the three new LDQ sub-scales designed to measure organisational context, follower commitment and leader performance; and the relationship between personality and leadership. Design/methodology/approach -Research is reported on LDQ data from a large sample of leaders and managers (n 222) from a range of public and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
241
3
18

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(297 citation statements)
references
References 21 publications
11
241
3
18
Order By: Relevance
“…Coaching focused leaders are supportive and provide non-defensive responses to questions and challenges (Savelsbergh et al, 2015). They invest time and effort in guiding the followers, identify new tasks and roles to develop their competencies, and believe that critical feedback and challenge are important (Dulewicz & Higgs, 2005).…”
Section: Person-focused Leadership Behaviorsmentioning
confidence: 99%
“…Coaching focused leaders are supportive and provide non-defensive responses to questions and challenges (Savelsbergh et al, 2015). They invest time and effort in guiding the followers, identify new tasks and roles to develop their competencies, and believe that critical feedback and challenge are important (Dulewicz & Higgs, 2005).…”
Section: Person-focused Leadership Behaviorsmentioning
confidence: 99%
“…The results revealed that, according to their subordinates, women displayed "feminine" leadership behaviors to a greater extent in organizations "numerically dominated by women" and dedicated to "typically feminine" activities than in the opposite case (male leaders, in organizations "numerically dominated by men" and dedicated to "typically masculine" activities). Recently, Dulewicz and Higgs (2005) investigated leadership style in relation to the leaders' sector, gender, function, nationality, and personality traits. The results revealed that the leadership styles were independent of these variables.…”
mentioning
confidence: 99%
“…Some researches suggest that in comparison with functional managers, project managers are assumed to have higher abilities in some areas such as crisis management and risk taking [6] [8]. They also argue that project managers are assumed to have a high degree of self esteem, EQ, and IQ to overcome above mentioned challenges.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a project manager"s job in most cases has a cross-functional nature which brings together experts from various functional groups into a team of diverse personalities and backgrounds [5]. Besides the mentioned differences, project managers are different from other managers in style of leadership and required competencies [6] [7] [8].…”
Section: Project Managers Vs Functional Managersmentioning
confidence: 99%